Pengembangan Kapasitas Dalam Rangka Peningkatan Kinerja BAPPEDA (Studi pada BAPPEDA Kabupaten Malang) - Kurniawan, Gigih (Jurnal Administrasi Publik, 2014)
Abstrak: Capacity Building in BAPPEDA Performance Improvement Framework (Studies in BAPPEDA Malang). This study sought to examine more deeply related BAPPEDA effort Malang to improve performance through capacity building that focuses on three aspects, namely: individual, organizational, and systems. Based on the data analysis it can be concluded that, capacity building in order to improve the performance BAPPEDA manifested in several ways, including: Improved performance in individual indicators realized by employee training, employee discipline presence, as well as employee rights record; Improved performance of the indicator is realized by rolling employee organization, social gathering, absorption, the ratio of the budget, the achievement of the program, and the revitalization of public communication; Improved performance of the indicator system. In this case realized with improved SOP, minutes of meetings, and the revitalization of PP 53 Year 2010. Keywords: capacity building, improved pervormance, BAPPEDA Malang Abstract: Pengembangan Kapasitas Dalam Rangka Peningkatan Kinerja Bappeda (Studi Pada Bappeda Kabupaten Malang). Penelitian ini berusaha mengkaji lebih dalam terkait upaya BAPPEDA Kabupaten Malang untuk meningkatkan kinerja melalui capacity building yang fokus pada tiga aspek,yakni: individu, organisasi, dan sistem. Berdasarkan analisis data dapat disimpulkan bahwa, capacity building BAPPEDA dalam rangka peningkatan kinerja diwujudkan dalam beberapa hal, antara lain: Peningkatan kinerja dalam indicator individu diwujudkan dengan diklat pegawai, presensi disiplin pegawai, serta catatan pelanggaran pegawai; Peningkatan kinerja dalam indikator organisasi diwujudkan dengan rolling pegawai, social gathering, penyerapan anggaran, rasio anggaran, pencapaian program, dan revitalisasi komunikasi publik; Peningkatan kinerja dalam indikator sistem. Dalam hal ini diwujudkan dengan perbaikan SOP, notulensi rapat, dan revitalisasi PP No. 53 Tahun 2010. Â  Kata kunci: Pengembangan Kapasitas, Peningkatan Kinerja, BAPPEDA Kabupaten Malang